HERMENEUTIKA DALAM PEMBELAJARAN PAI MEMBACA ULANG TEKS KEAGAMAAN SECARA KONTEKSTUAL - Muhammad Zaki (Yayasan An-Nur Meunara Baro, 2025)
Islamic Religious Education (PAI) has long been dominated by textual and normative approaches, which often limit students ability to understand religious texts in ways that are contextual and relevant to their social realities. This article aims to analyze how a hermeneutical approach can be utilized as a pedagogical strategy to reinterpret religious texts more dynamically and reflectively. This study employs a qualitative method through library research by reviewing the works of contemporary Muslim thinkers and recent research on the application of hermeneutics in Islamic education. The findings indicate that a hermeneutical approach emphasizing dialogue between text, context, and reader enhances students’ comprehension of Islamic values and fosters critical thinking, tolerance, and responsiveness to contemporary challenges. Furthermore, the integration of hermeneutics into the Islamic education curriculum enriches teaching models and strengthens students' reflective capacity. The study concludes that hermeneutics can serve as a methodological alternative for developing Islamic education that is more inclusive, contextual, and meaningful.